Trophic structure of shallow-water benthic communities in the sub-Antarctic Strait of Magellan - Andrade Diaz, Claudia Daniela Yanett; Gerdes, Dieter; Rios Cardoza, Carlos Francisco; Brey, Thomas (My University, 2016)
Trophic structure is among the most fundamental characteristics of an ecosystem since it is a useful way to determine the main energy flow at the ecosystem level. In the Magellan Strait, the local spatial heterogeneity at the shallow-waters ecosystems may have a great variety of potential food sources; however, knowledge about their biological communities and their structure is still unclear. We examined the trophic structure of shallow-water-mixed bottom communities at two sites in the sub-Antarctic Magellan Strait based on carbon (delta C-13) and nitrogen (delta N-15) stable isotope ratios. The benthic communities were composed of 46 species from 20 major taxa at Bahia Laredo (BL) and 55 species from 18 major taxa at Punta Santa Ana (PSA). Benthic macroalgae and organic matter associated with sediment are the major primary food sources at both sites. Although both sites are quite similar in their food sources and in their vertical trophic structure (>= three trophic levels), the food web structure varied distinctly. Functionally, predators and grazers dominated both communities, but top predators were shorebirds, carnivore anemones and predatory nemerteans at BL, and sea stars, shorebirds, crabs and fishes at PSA. The distinct differences in the trophic structure at BL and PSA highlight the important variability of delta N-15 at the base of the benthic food web, the role of local environmental conditions and community dynamics in structuring shallow-water communities.
Keywords: benthic communities; functional guilds; isotopic niche; magellan strait; stable isotope; subpolar; trophic ecology